Optimalisasi Program Edukasi Pencegahan Stroke ‘Cerdik’ pada Penderita Hipertensi: Optimizing the 'Smart' Stroke Prevention Education Program for Hypertension Sufferers - Laili, Nurul; Heni, Sutiyah; Tanoto, Wahyu (Jurnal Abdi Keperawatan dan Kedokteran, 2023)
Hypertension is a disease that can cause complications, one of which is stroke. These complications can be prevented by controlling and self-care through stroke prevention education programs. Knowledge in self-care in patients with chronic diseases is needed for the successful management and control of these chronic diseases. The purpose of community service activities is to provide education on how to prevent stroke complications in people with hypertension so that disease complications can be prevented optimally. The education was held on April 28-29 2023, in Darungan Village, Pare District, Kediri Regency. Counseling participants who followed as many as 35 people. The number of students who took part in the activity was 5 students. The methods used are lectures, discussions/questions and answers with the media of leaflets, videos. Explanation of the material using LCD media and laptops. The results of filling out questionnaires about stroke prevention programs in hypertension sufferers found that most of them had good knowledge after being educated. Stroke prevention educational programs can be carried out through health promotion activities. Education.